La condizione dei Rom (RSC) in Italia tra processi di discriminazione, esclusione e segregazione lavorativa - Omizzolo, Marco; Sodano, Pina (SocietàMutamentoPolitica, 2026)
The essay summarizes the data collected in a research, which is still in progress, conducted by the Tempi Moderni study centre on the condition of the Rom communities in Italy. It is based on two fundamental theses. First of all, on the fact that the system of inequalities experienced by Rom people is multidimensional. These dimensions influence each other on a material level and turn the relationship between cause and effect, legitimising widespread prejudice and discrimination against the Rom community. These prejudices are reconstructed also from a historical point of view, and the essay focuses mainly on employment and housing inequality. The second thesis analyzes the system of complex disparities affecting Rom communities within the system of inequalities and discriminations typical of Italian and global society. Inequality, poverty and work segregation are therefore the consequences of political choices aimed at marginalizing the numerous Rom communities and legitimizing widespread and dangerous commonplaces and prejudices.